KEPADATAN SARANG GALO-GALO (Trigona spp.) DI KELURAHAN BALAI GADANG KECAMATAN KOTO TANGAH PADANG SUMATRA BARAT - Agusnadi, Adi - (STKIP PGRI Sumbar, 2014)
Galo Galo (Trigona spp.) are able to adapt in a variety of locations and a variety of housing types of bamboo houses, wood to stone, these insects breed rapidly. In addition, population-galo galo bees require a fairly moist air. In connection with it has conducted research on nest density Galo-Galo (Trigona spp.) in the Village Hall Tower, District Koto Tangah, Padang in West Sumatra in December 2013 and ending in January 2014. This study used a descriptive survey method to measure the density of nests found in the study site and the purpose of this research is to look at the density of nest-galo galo (Trigona spp.), The character of nesting and food resources bee plant species found on the study site, From the research found that the number of nests 3 2 cottage home in plantation and one in houses with an average of 1 / ha. gate length ranging from 13.8 mm to nest with 32.2 mm, a height of 142 cm soil surface ranges up to 203 cm and a diameter ranging from 6.2 mm gate nest up to 11.8 mm.